THE INERTIA FORCE EQUILIBRIUM ANALYSIS OF CRANK-GROUP DRIVING MECHANISM - WU Yao; CAO JuJiang; YAN WeiLiang; XI WenJun (Jixie qiangdu)
Aiming at overcoming the deficiency of balance of the Crank-group Driving Mechanism,utilize Mass moment substitution method to translate the equilibrium problem of inertia force of Crank-group Driving Mechanism into the additional mass moment of branch member（ connecting rod truss） in the adjacent cranks and the balance of two pair rod tree system that composed of all cranks in mechanism. The inertia force equilibrium condition for any Crank-group Mechanism can be listed directly by combining the formulas of the mass moment substitution formula of connecting rod truss and the inertia force balancing equation of arbitrary crank in the mechanism,then take Four-Cranks Mechanism as an example to simplify the equilibrium conditions that provide a theoretical basis for different structure form of cranks in the mechanism. Finally,use 3D modeling software Pro / E and dynamics analytic software ADAMS to verify the balance applicability for Crank-group Driving Mechanism.